Erich Uhmann: Publications and Proposed Taxa in the Hispinae (Coleoptera: Chrysomelidae). - Staines, Charles L. (Contributions to Entomology = Beiträge zur Entomologie, 1997)
A biographical sketch, bibliography of 235 hispine articles, and list of proposed Hispinae taxa (5 tribes, 39 genera, 606 species, and 61 subspecies) are presented for Erich Uhmann. Keywords Uhmann, biography, bibliography, proposed taxa.